(untitled) (The Review of Diabetic Studies, 2025)
This study aims to identify the impact of work culture and career transformation on the efficiency of ambulance teams in dealing with major accidents in rural areas. The study relied on the descriptive analytical approach, where a questionnaire consisting of five items was applied to a sample size of (200) individuals working in ambulance teams. The results showed a high level of agreement among sample members that a positive work culture and continuous professional transformation contribute significantly to improving the efficiency of ambulance teams by enhancing rapid response capacity, reducing errors, and improving the quality of service provided. The results also showed that the item with the highest arithmetic mean was “Continuous professional transformation improves service quality” with an average of (4.25), while the lowest item was “Benefiting from the exchange of professional experiences between teams” with an average of (4.12), yet both remained within the high level. The study recommends investing in ongoing training and qualification programs and promoting a culture of collaborative work to enhance the preparedness of ambulance teams to respond to crises in rural areas.